Advance Methodology for Effective Implementation of Ambidextrous Innovation Culture - AlSaied, Mohammad; McLaughlin, Patrick; Alkhoraif , Abdullah (Journal of Ecohumanism, 2024)
The organizations are facing a challenge of sustaining long-term business performance. As literature suggests, such long-term business performance can be attained through innovation. The ambidextrous innovation framework appears to be a key strategic framework that organizations can adopt in order to sustain their long-term business performance. Ambidextrous innovation is impactful because it helps organizations carry out both radical innovation, referred to as explorative, and incremental innovation, often referred to as exploitative innovation. However, implementing and adopting such a framework presents significant challenges that organizations have to face. Early insights and theories suggest that innovation, and more specifically ambidextrous innovation, requires a conducive culture that promotes behavioral patterns such as risk-taking, application of new ideas, collaboration, and cooperation. In light of such insights, the aim of the present research is to build the methodological toolbox to extract key insights and build theoretical models that assess the relationship between ambidextrous innovation and organizational culture. More specifically, this research guides organizations in modeling the culture so it can facilitate the implementation of ambidextrous innovation. The methodological stance and guidelines suggest that key grounded theory and action research methodologies of qualitative research can be employed to collect and analyze the data, leading to a theoretical model explaining the nuances of the culture necessary for the adaptation and implementation of ambidextrous innovation.